1982
DOI: 10.1037/0033-2909.92.2.410
|View full text |Cite
|
Sign up to set email alerts
|

The role of anger and hostility in essential hypertension and coronary heart disease.

Abstract: A critical review of the literature pertaining to the role of anger and hostility in essential hypertension and coronary heart disease is presented. Psychodynamic, personality, and psychophysiological approaches are covered. Anger and hostility appear to play an important role in the development of hypertension, though the mechanism is not yet clearly specified. In the coronary heart disease literature, aggression is more commonly referred to than anger; recent evidence suggests, however, that hostility may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0
5

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(137 citation statements)
references
References 151 publications
6
126
0
5
Order By: Relevance
“…Forgiveness frees others from their guilt, expedites, the resolution of depressive episodes, and leads to a decrease in anxiety as anger is released. It improves the ability to express anger appropriately, as the degree of repressed anger diminishes and resolves many of the physical illnesses caused by anger (Barefoot et al, 1983;Dembroski et al, 1985;Diamond, 1982;Madow, 1972;Shekelle et al, 1983;Smith et al, 1984).…”
Section: Forgivenessmentioning
confidence: 99%
“…Forgiveness frees others from their guilt, expedites, the resolution of depressive episodes, and leads to a decrease in anxiety as anger is released. It improves the ability to express anger appropriately, as the degree of repressed anger diminishes and resolves many of the physical illnesses caused by anger (Barefoot et al, 1983;Dembroski et al, 1985;Diamond, 1982;Madow, 1972;Shekelle et al, 1983;Smith et al, 1984).…”
Section: Forgivenessmentioning
confidence: 99%
“…Across the studies of cardiovascular disease and negative health outcomes, the common denominators which have Correlational studies have found a positive association between self-reported reluctance to express anger openly, and higher resting blood pressure (Diamond, 1982;Harrell, 1980;Harburg, Blakelock, & Roeper, 1979; Heiner, 1977;Baer, Collins, Bourianoff, & Ketchel, 1979), as well as elevations in baseline blood pressure under stress (Harburg et al, 1979; Gentry, Chesney, Gary, Hall, & Harburg, 1982). .…”
Section: Cardiovascular Reactivitymentioning
confidence: 99%
“…This finding is supported by other researchers as well (Kahn, Medalie, Neufeld, Riss, & Goldbourt, 1972; McClelland, 1979; Falkner et al, 1979 Equally as important as the frequency and amount of anger experienced is the expression of the feelings, often described as "anger-in," and "anger-out." Anger-in is defined as "an unwillingness in a variety of oircumstances to express frustration-induced hostility and/or anger overtly, especially if the potential for interpersonal conflict would be heightened by such behavior" (Dembrosxi, MacDougall, Williams, Haney, & Blumenthal, 1985, p. 230)._ Conversely, anger-out is openly directed towards the source.Across the studies of cardiovascular disease and negative health outcomes, the common denominators which have Correlational studies have found a positive association between self-reported reluctance to express anger openly, and higher resting blood pressure (Diamond, 1982;Harrell, 1980;Harburg, Blakelock, & Roeper, 1979; Heiner, 1977;Baer, Collins, Bourianoff, & Ketchel, 1979), as well as elevations in baseline blood pressure under stress (Harburg et al, 1979; Gentry, Chesney, Gary, Hall, & Harburg, 1982). .…”
mentioning
confidence: 99%
“…Examples of items include -I am not likely to speak to people until they speak to me‖ and -I am often inclined to go out of my way to win a point with someone who has opposed me.‖ The coefficient alpha was equal to .87 and .82 for the dating and married samples, respectively. The Ho scale has been widely used to study hostility in samples of newlywed couples Smith & Frohm, 1985), and is predictive of later cardiovascular disease outcomes and general mortality (e.g., Dembroski & Costa, 1987;Diamond, 1982). High scores on this measure indicate higher levels of trait hostility.…”
Section: Methodsmentioning
confidence: 99%